Responsible Investing in South African Collective Investment Schemes: An Analysis of Performance - Killingbeck, Charles William Jack (Graduate School of Business (GSB), 2024)
Estimates suggest that a $3.3 - $4.5 trillion financing gap exists if we are to meet the SDG goals by 2030. Public funding alone cannot meet this target, private capital needs to be mobilised. Impact investing has the potential to bridge this gap, providing measurable real-world impact alongside financial performance. However, the empirical effect of impact investing on financial performance appears under researched. This study sought to identify if funds, and investors, accept a trade-off between impact and financial performance among Collective Investment Schemes (CISs) domiciled in South Africa. The quasi-experimental design, with the two methods of analysis being a non-parametric ANOVA and multiple regression (OLS and fixed effects) were employed to analyse data on 1,106 South African Collective Investment Schemes over three- and five-year investment periods. The results indicate a weak relationship with the absolute returns performance measure, both positive and negative, but fail to establish a relationship for volatilities and risk-adjusted returns. The latter suggests that measurable real-world impact can be attainted alongside financial performance. These findings will improve individual investor's and investment manager's understanding of responsible investing, ESG factors and the relationship with risk and returns and, importantly, they indicate the financial performance barrier does not appear to exist in South African CISs